PERAN MUROBBI DALAM MANAJEMEN PRIVASI KOMUNIKASI UNTUK MEMPERTEMUKAN JODOH: (Studi Kasus Pada Pasangan Ta'aruf Wahdah Islamiyah Makassar) - Muhammad Khalil Gunawan (Jurnal Dakwah Tabligh, 2022)
Marriage through the culture of ta'aruf at Wahdah Islamiyah has become an obligation for every fostered cadre who has been nurtured by Murobbi and has the desire to get married. The purpose of this study was to determine the role of Murobbi as a mediator and Co-Owner of Personal Information that is exchanged for ta'aruf couples who want to get married. The personal disclosure happened to the ta'aruf Wahdah Islamiyah couple to Murobbi by maintaining their privacy. This phenomenon is being studied with the theory of Communication Privacy Management. The research method used is descriptive qualitative with a case study approach. Two types of data sources were used in this research phase, namely primary data and secondary data, then the data was analyzed using Miles and Huberman data analysis. The results of this study found that biodata and photos as personal information were exchanged by Murobbi (Co-Owner of personal information) in controlling the exchange of information with prospective ta'aruf partners through roles built by murobbi, namely as parents, teachers, friends, and The leader shows that 1) the trust given in choosing a mate 2) maintaining communication boundaries and photo privacy, 3) controlling access to private information, 4) managing the disclosure of personal information in providing solutions for prospective ta'aruf partners Keywords: Murobbi’s Role, Personal Information, Photo Privacy Resrictions